Pengaruh Kepercayaan Konsumen dan Kualitas Pelayanan terhadap Keputusan Pembelian Pulsa dan Voucher di Konter Anggun Cell - Nenny Dwi Mahardini; Aditya Liliyan (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to analyze the effect of consumer trust and service quality on purchasing decisions of mobile credit and vouchers at Anggun Cell Counter. Despite the rapid growth of digital payment platforms, physical mobile credit counters continue to play an important role, especially for consumers who prefer direct transactions and personal interaction. This research employed a quantitative approach with an explanatory research design. Primary data were collected through questionnaires distributed to 130 respondents who were customers of Anggun Cell Counter in Juwiring District, Klaten Regency. The sampling technique used purposive sampling, targeting respondents aged 18-40 years who had made at least one purchase. Data analysis was conducted using multiple linear regression with SPSS Statistics 27. The results indicate that consumer trust and service quality have a positive and significant effect on purchasing decisions. Among the two variables, service quality shows a more dominant influence on consumer purchasing decisions. These findings confirm that relational factors and service experiences remain crucial determinants of purchasing decisions in offline mobile credit retail businesses. This study provides empirical evidence that enriches the literature on service marketing and consumer behavior, while also offering practical insights for MSME owners to enhance service performance and build sustainable consumer trust.